Estudos experimentais da punição de tato como condição favorecedora da extensão metafórica - Carvalho, Filipe Cesar da Hora (Universidade Federal de São Carlos, 2024)
Metaphor is a figure of speech that can be studied in two ways in Behavior Analysis: by examining the effect of metaphors on the listener and by analyzing the production or emission of metaphor. The production of metaphor is studied under the label of the metaphoric extension of the verbal operant tact. Metaphoric extension is a type of generalization of the tact, in which the properties of the stimulus that control the verbal response are adventitious. It is considered that the development and refinement of experimental procedures to study metaphoric extension are highly relevant for understanding human behavior and for the scientific advancement of the field. This study aimed to refine a new experimental procedure developed to examine the conditions in which metaphoric extension is emitted more frequently. A previous study, in a design with three experimental phases, found that punishment increased the frequency of metaphor emission. The study's results showed the method's efficacy, but it still had some limitations and required some experimental refinements. Therefore, the objectives of this study were: (1) to verify whether the presentation of adventitious properties without punishment affects the frequency of metaphoric extension emission (Experiment 1 and Experiment 2); (2) to analyze the frequency of metaphoric extension emission under the condition of point loss (Experiment 3); and to analyze the effect of punishment on the frequency of metaphor emission by typing. In all experiments, the procedures were divided into five experimental phases as follows: in the first two phases, Tact Training with Prompt and Tact Training, participants learned to emit the tact for stimuli from four different classes. After reaching the learning criterion, a phase called Test 1 began. This phase assessed the frequency of metaphoric extension emission of tacts learned in the previous phase, in a condition without differential consequences for all of the emitted tacts. Then, in the Punishment phase, one of the tacts was punished, and the effects on the frequency of metaphoric extension of other tacts were observed. Finally, a phase called Test 2 began, which assessed the frequency of metaphoric extension in a condition without differential consequences. Small methodological changes were added in each experiment: in Experiment 1, the insertion of the first test phase; in Experiment 2, the addition of exemplars from one of the stimulus classes and alteration of the required response topography; in Experiment 3, the use of point loss and gain consequences; and finally, in Experiment 4, the verbal responses were typed rather than selected. The results of the experiments showed an increase in the frequency of metaphor emission without punishment (Experiment 1) and with punishment in all experiments. The effects of punishment and the effect of pre-experimental conditions on the frequency of metaphoric extension emission were discussed.
Experimental studies on the punishment of tact as a favorable condition for metaphoric extension
Keywords: Metaphor; Tact; Metaphorical extesion; Adventitious properties; Punishment; Metáfora; Tato; Extensão metafórica; Propriedades adventícias; Punição; CIENCIAS HUMANAS::PSICOLOGIA